Postural adjustment errors reveal deficits in inhibition during lateral step initiation in older adults - Sparto, Patrick J. (American Physiological Society, 2013)
Postural dual-task studies have demonstrated effects of various executive function components on gait and postural control in older adults. The purpose of the study was to explore the role of inhibition during lateral step initiation. Forty older adults participated (range 70–94 yr). Subjects stepped to the left or right in response to congruous and incongruous visual cues that consisted of left and right arrows appearing on left or right sides of a monitor. The timing of postural adjustments was identified by inflection points in the vertical ground reaction forces (VGRF) measured separately under each foot. Step responses could be classified into preferred and nonpreferred step behavior based on the number of postural adjustments that were made. Delays in onset of the first postural adjustment (PA1) and liftoff (LO) of the step leg during preferred steps progressively increased among the simple, choice, congruous, and incongruous tasks, indicating interference in processing the relevant visuospatial cue. Incongruous cues induced subjects to make more postural adjustments than they typically would (i.e., nonpreferred steps), representing errors in selection of the appropriate motor program. During these nonpreferred steps, the onset of the PA1 was earlier than during the preferred steps, indicating a failure to inhibit an inappropriate initial postural adjustment. The functional consequence of the additional postural adjustments was a delay in the LO compared with steps in which they did not make an error. These results suggest that deficits in inhibitory function may detrimentally affect step decision processing, by delaying voluntary step responses.